DIFFERENTIAL DIAGNOSIS DIFFICULTIES GYNECOLOGICAL AND SURGICAL PATHOLOGY IN ADOLESCENT GIRLS BEING TREATED AT CHILDREN'S DEPARTMENT IN MULTIDISCIPLINARY HOSPITAL - Вадим Александрович Дударев; Дмитрий Александрович Маисеенко; Марина Юрьевна Галактионова (The Publishing House Medicine and Enlightenment, 2016)
The article presents the analysis of differential diagnosis of gynecological and surgical pathology in adolescents who were treated in inpatient pediatric wards at the General Hospital. All teenage girls surgeries were performed: laparoscopic appendectomy was performed in 88 %, and diagnostic laparoscopy - in 12 % of cases. The difficulty in the differential diagnosis of abdominal symptoms in adolescent girls should necessarily include an examination of children's surgeon and gynecologist with child holding ultrasound retroperitoneal, abdominal and pelvic organs. Laparoscopy, to date, in case of doubt, can not only correctly establish the presence or absence of inflammation of the appendix, but also to the exclusion of the diagnosis of acute appendicitis to conduct an audit of the abdominal cavity, and the majority of patients to identify the true cause of abdominal pain syndrome. Patients, who underwent surgery for acute appendicitis in conjunction with inflammatory diseases of the uterus, should form a separate group of dispensary.